Raza studies : the public option for educational revolution - Cammarota, Julio; Romero, Augustine; Stovall, David (University of Arizona Press, 2014)
"The well-known and controversial Mexican American studies (MAS) program in Arizona's Tucson Unified School District set out to create an equitable and excellent educational experience for Latino students. This book offers the first comprehensive account of this progressive program by those who created it, implemented it, and have struggled to protect it"--